Growing the values of nationalism from early childhood through learning the national anthem - Herman Yuliandoko; Abdul Rohman; Ninik Sri Rahayu (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Early Childhood Education is a very important period in forming one's character. Moreover, the education of the main character of nationalism must be instilled early on because the global challenges in this era are enormous. There are several methods of learning nationalism in early childhood, one of which is learning through singing. Currently, in Kindergarten Dinar Nasyiah 2 Rogojampi, nationalism education is still lacking because facilities are constrained by infrastructure and teacher skills. This problem encouraged the community service team to carry out this activity. It is hoped that this will increase the participants' knowledge and improve school facilities that can support the growth of national values from an early age. This activity is carried out through workshops and training for teachers, students, and parents of students. From the implementation of these activities, it can be seen that all participants were very enthusiastic to participate. In addition, the teachers felt they were getting additional knowledge about nationalism learning methods for children. This activity also gave rise to a new extracurricular activity at school, namely the drum band for Kindergarten students Dinar Nasyiah 2 Rogojampi.